2019
DOI: 10.1016/j.celrep.2019.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Soma-Derived Degradative Lysosomes Are Continuously Delivered to Distal Axons to Maintain Local Degradation Capacity

Abstract: SUMMARY Neurons face the challenge of maintaining cellular homeostasis through lysosomal degradation. While enzymatically active degradative lysosomes are enriched in the soma, their axonal trafficking and positioning and impact on axonal physiology remain elusive. Here, we characterized axon-targeted delivery of degradative lysosomes by applying fluorescent probes that selectively label active forms of lysosomal cathepsins D, B, L, and GCase. By time-lapse imaging of cortical neurons in microfluidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
130
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(149 citation statements)
references
References 78 publications
14
130
0
Order By: Relevance
“…LAMP1 is concentrated mainly in lysosomes, although significant amounts are also found in early and late endosomes ( Fermie et al, 2018 ), a reflection of its transport to lysosomes via the endocytic pathway ( Lippincott-Schwartz and Fambrough, 1987 ; Janvier and Bonifacino, 2005 ; Chen et al, 2017 ). In axons, LAMP1-positive vesicles are heterogeneous, with some having an acidic luminal pH and acid hydrolases (i.e., conventional lysosomes), while others are neutral and lack acid hydrolases ( Lee et al, 2011 ; Gowrishankar et al, 2015 ; Farías et al, 2017 ; Cheng et al, 2018 ; Vukoja et al, 2018 ; Farfel-Becker et al, 2019 ). This heterogeneity notwithstanding, for simplicity, herein we refer to all LAMP1-positive vesicles as lysosomes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…LAMP1 is concentrated mainly in lysosomes, although significant amounts are also found in early and late endosomes ( Fermie et al, 2018 ), a reflection of its transport to lysosomes via the endocytic pathway ( Lippincott-Schwartz and Fambrough, 1987 ; Janvier and Bonifacino, 2005 ; Chen et al, 2017 ). In axons, LAMP1-positive vesicles are heterogeneous, with some having an acidic luminal pH and acid hydrolases (i.e., conventional lysosomes), while others are neutral and lack acid hydrolases ( Lee et al, 2011 ; Gowrishankar et al, 2015 ; Farías et al, 2017 ; Cheng et al, 2018 ; Vukoja et al, 2018 ; Farfel-Becker et al, 2019 ). This heterogeneity notwithstanding, for simplicity, herein we refer to all LAMP1-positive vesicles as lysosomes.…”
Section: Resultsmentioning
confidence: 99%
“…Lysosomes are membrane-bound, acidic organelles that are primarily involved in intracellular degradation of biomacromolecules but also participate in various non-degradative processes such as nutrient and growth factor signaling and plasma membrane repair ( Ballabio and Bonifacino, 2020 ). Axonal lysosomes are particularly heterogeneous with regard to their degradative capacity and acidity ( Lee et al, 2011 ; Gowrishankar et al, 2015 ; Farías et al, 2017 ; Cheng et al, 2018 ; Farfel-Becker et al, 2019 ), a property that may reflect the existence of populations of lysosomes with distinct functions or maturational states ( Ferguson, 2019 ). In mammals, anterograde lysosome transport depends on coupling to several members of the kinesin family, especially the kinesin-1 proteins KIF5A, KIF5B, and KIF5C, and kinesin-3 proteins KIF1A and KIF1Bβ ( Nakata and Hirokawa, 1995 ; Tanaka et al, 1998 ; Matsushita et al, 2004 ; Guardia et al, 2016 ; Farías et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…This retrograde transport of autophagosomes along the microtubule is dynein-and activity-dependent in granule cells (Katsumata et al, 2010). It was recently reported that soma-derived degradative lysosomes are anterogradely transported to the distal axon to fuse with autophagosomes to form autolysosomes, which are later retrogradely transported to the soma for degradation in mouse cortical neurons at DIV 14 (Farfel-Becker et al, 2019). In disease neurons, impaired axonal delivery of lysosome causes autophagic stress.…”
Section: Autophagy-endolysosomal Network Defects In Tauopathymentioning
confidence: 99%
“…Indeed, accumulation of lysosomes, lysosomal hydrolases, autophagosome, autophagic vacuoles, multi-vesicular bodies (MVBs), autolysosomes, and defect in lysosomal membrane integrity in the brain has been reported in AD, CBD, and PSP patients (Nixon et al, 2005;Nixon, 2013;Piras et al, 2016;Menzies et al, 2017). Defects in the retrograde transportation of autophagosomes from axon to soma and antegrade transportation of degradative lysosomes to distal axons were also demonstrated (Farfel-Becker et al, 2019). On the other hand, fragmented tau can impair CMA and lysosomal dysfunction and lead to tau oligomerization and aggregation (Wang et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…To regulate function, polarized neurons rely largely on active microtubule-based transport to localize components to distal axonal domains via kinesin-mediated anterograde movement 3 . As the axon has important but limited lysosomal degradative capacity 4 , long-distance dynein-dependent retrograde transport of axonal cargoes back to the lysosome-enriched soma is critical for their efficient degradation 5, 6 . Neuronal homeostasis also depends on an interconverting endo-lysosomal system that spreads over long axonal distances, to regulate sorting, signaling, and metabolic functions 7 .…”
Section: Introductionmentioning
confidence: 99%